Interplay between Plasmodium falciparum haemozoin and l-arginine: implication for nitric oxide production - Corbett, Yolanda (Malar J, 2018)
BACKGROUND: Plasmodium falciparum haemozoin, a detoxification product of digested haemoglobin from infected erythrocytes, is released into the bloodstream upon schizont rupture and accumulates in leukocytes. High levels of haemozoin correlate with disease severity. Some studies have shown that concentrations of the substrate of inducible nitric oxide synthase (iNOS), l-arginine, as well as nitric oxide are low in patients infected with P. falciparum malaria. The present study investigates, in vitro, the role of P. falciparum haemozoin on nitric oxide production, iNOS expression in macrophages, and the possible interaction between l-arginine and haemozoin. METHODS: Plasmodium falciparum haemozoin was obtained from in vitro cultures through magnetic isolation. Phagocytosis of haemozoin by immortalized bone marrow derived macrophages was detected by confocal reflection combined with fluorescence microscopy. Nitrite concentrations in the supernatants was evaluated by Griess assay as a standard indication of nitric oxide production, while iNOS expression was detected on cell extracts by western blotting. Detection of l-arginine in haemozoin-treated or untreated media was achieved by liquid chromatography–tandem mass spectrometry (LC–MS/MS). RESULTS: Haemozoin synergizes in vitro with interferon-gamma to produce nitric oxide. However, when mouse macrophages were stimulated with haemozoin, a proportional increase of nitric oxide was observed up to 25 μM of haemozoin, followed by a decrease with doses up to 100 μM, when nitric oxide release was completely abrogated. This was not due to reactive oxygen species production, nor to an effect on iNOS activity. Interestingly, when at 24 h, haemozoin-treated macrophages were washed and incubated in fresh medium for further 24 h, the nitric oxide production was restored in a dose–response manner. Similar results were seen when l-arginine-enriched media was used in the stimulation. Moreover, muramyldipeptide, a strong nitric oxide inducer, was unable to activate macrophages to release nitric oxide in the presence of haemozoin-treated medium. By LC–MS/MS a complete depletion of l-arginine was observed in this haemozoin-treated, conditioned medium. CONCLUSIONS: It is proposed that haemozoin interacts with l-arginine reducing its availability for iNOS, and thus decreasing nitric oxide production. The clinical (or pathological) implications of these results are discussed. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12936-018-2602-0) contains supplementary material, which is available to authorized users.